WATER QUALITY IN MADURA STRAIT, INDONESIA - Nugrahadi, M. Saleh; Yanagi, Tetsuo (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2003)
Observations on water quality based on physical chemical and biological properties of sea surface water were conducted on 13-14 September 2000 and on 14-15 May 2001 in Madura Strait, Indonesia. Particular emphasis has been placed on Surabaya and Porong estuaries and its surrounding coastal water, where rivers carry contaminated load from land and debouch. The observation showed that Madura Strait received a lot of pollutant from the rivers.